Studi Kasus Harga Diri Perempuan Terlecehkan Dalam Adaptasi Kerja - Budi, Maximillianus Yosep Hendrawan Setya; Barus, Gendon (Mahesa Research Center, 2025)
This study aims to explore the role of self-esteem in the psychological adaptation and work mobility of a young woman who experienced risky social behavior and sexual harassment during her adolescence. The research employed a qualitative approach with a single case study method. The subject is a 23-year-old woman working in the food service sector. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings reveal that self-esteem plays a crucial role in the subject's psychological recovery and career decision-making. Positive adaptation was supported by social support, self-reflection, and empowering work experiences that strengthened her identity. In conclusion, healthy self-esteem is a key foundation in the post-trauma recovery process and contributes to more reflective and empowering career mobility.